Teacher’s Role as Motivator in the Development of Students at Neglasari Cipare Primary School, Serang, Indonesia - Syifa Hayatunnisa Anwar; Hana Sela Ijie (Community Medicine and Education Journal, 2023)
Apart from serving as a teacher, the teacher also acts as a mentor, guide, and motivator who helps students achieve their best potential. Motivation is the key to increasing student interest, participation, and learning achievement. This study aimed to assess the teacher's role as a motivator for students in Neglasari primary school. This study is qualitative observational research. Research requires assistance instruments, namely screening forms, informant data, interview guidelines, and recording equipment, which in this study required primary data and secondary data. Teachers have a key role in arousing and maintaining student motivation. Teachers can create a fun, inclusive, and positive classroom environment. Teachers must provide clear and structured goals to students. Teachers must use a variety of interesting and varied teaching methods. Teachers must provide constructive and positive feedback to students. Teachers can use a personalized approach to teaching. Teachers can help students see the relevance of the subject matter to the real world.